A Correction - Gold Dredging In California And Methods Devised To Increase Recovery - E. S. Leaver (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1937)
The authors of the paper above mentioned have sent the following statement to correct erroneous com-ments and implications in their article with the re-quest that it be published: "In the above mentioned article the reference to Bendelari jigs is used in the generic sense as applying to the mechanically driven diaphragm jigs. No attempt was made to dif-ferentiate between the various machines as installed on different dredges. The Natomas Company use a jig of their own manufacture. The Yuba Company installed the Placer jig as manufactured by the Pan American Engineer-ing Company. "The Pan American Engineering Company also manufactures the Crangle jig under their own name. This is a diaphragm jig in which the pulsations are produced by intermittent flow of water through the patent Crangle Valve and it has no driving mechanism."